2021
DOI: 10.1063/5.0045449
|View full text |Cite
|
Sign up to set email alerts
|

Modeling laser-driven ion acceleration with deep learning

Abstract: Developments in machine learning promise to ameliorate some of the challenges of modeling complex physical systems through neural-network-based surrogate models. High-intensity, short-pulse lasers can be used to accelerate ions to mega-electronvolt energies, but to model such interactions requires computationally expensive techniques such as particle-in-cell simulations. Multilayer neural networks allow one to take a relatively sparse ensemble of simulations and generate a surrogate model that can be used to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…This approach has already been demonstrated to improve electron and X-ray beams from wakefield accelerators [65,66] and laser-driven proton acceleration in simulations [67] . Other machine learning techniques that have been applied in the study of laserplasma accelerators include neural networks [68,69] and evolutionary algorithms [70][71][72][73] .…”
Section: Optimizationmentioning
confidence: 99%
“…This approach has already been demonstrated to improve electron and X-ray beams from wakefield accelerators [65,66] and laser-driven proton acceleration in simulations [67] . Other machine learning techniques that have been applied in the study of laserplasma accelerators include neural networks [68,69] and evolutionary algorithms [70][71][72][73] .…”
Section: Optimizationmentioning
confidence: 99%
“…With the proliferation of multi-Hz high power laser pulses [34], and the development of HRR-compatible solid-density targetry [35][36][37][38][39][40][41], it is now possible to quickly obtain large datasets from laser-driven ion acceleration experiments. This opens the possibility to perform extensive multi-dimensional parameter scans to elucidate the interdependence of different experimental control parameters, as well as to apply machine learning techniques to optimise ion beam properties -within complex multi-dimensional parameter spaces -in automated experiments [42][43][44] and simulations [45,46].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the context of plasma-based ion acceleration it has further been shown that surrogate models can replace costly simulations, based on training neural networks with comparably sparse sets of particle-in-cell simulations [305,306].…”
Section: H Control and Optimisation Of Plasma Accelerator Experimentsmentioning
confidence: 99%